PARAMETER EVALUATION AND CONTROL IN AN ELECTRO-HYDRAULIC SYSTEM USING AN ADVANCED LEAST SQUARES METHOD (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Electro-hydraulic systems are characterized by high complexity and nonlinearity, caused by the dynamic interactions between the fundamental quantities that determine their operation and control. The present study proposes a method for adaptive parameter estimation using an advanced method of least squares (A-LS) (Advanced Least Squares), applicable to nonlinear dynamical systems. The paper presents a mathematical model describing the dynamics of the electro-hydraulic system, as well as an approach for adaptive parameter estimation using Recursive Least Squares (RLS) in combination with the Stochastic Gradient Method (SGD). The main goal is to minimize errors between measurement results and predicted model values, ensuring high accuracy and stability under variable operating conditions. The results of the simulations show that the use of RLS for angular velocity estimation and SGD for adaptive load torque correction allows for effective noise suppression in measurements and precise tracking of system dynamics. The proposed approach provides a basis for optimizing electro-hydraulic systems through adaptive methods and can be useful for applications requiring high accuracy and reliability.